(untitled) (Stavební obzor - Civil Engineering Journal, 2019)
This paper presented results of a numerical study on seven designs of T shape fishways. The trajectory equation of the maximum velocity line and the V/Va equation of the T shape fishways were obtained from the results. It was found that a width of 1.5bs for the T lateral baffle, a width of 5bs and a length of 6.25bs for the pools were very satisfactory for the dimensional design of T shape fishways, where bs was the slot width. From the seven designs studied, design 3 (D3, D denotes “design”) was recommended for practical use.